Low Omega-3 Levels in the Diet Disturbs Intestinal Barrier and Transporting Functions of Atlantic Salmon Freshwater and Seawater Smolts - Sundell, Kristina; Berge, Gerd Marit; Ruyter, Bente; Sundh, Henrik (Frontiers in Physiology, 2022)
Due to a limited access to marine raw materials from capture fisheries, Atlantic salmon feeds are currently based on mainly plant ingredients (75%) while only 25 % come from traditional marine ingredients including marine fish meal and fish oil. Thus, current feeds contain less of the essential omega-3 fatty acids. The aim of the study was to assess the impact of different omega-3 levels in fish feed on intestinal barrier and transporting functions of Atlantic salmon freshwater and seawater smolts. Atlantic salmon were fed three levels of omega-3 (2%, 1% and 0.5%) and fish performance was followed through smoltification and the subsequent seawater acclimation. Intestinal barrier and transporting functions were assessed using Ussing chamber methodology and combined with transcript analysis of tight junction related proteins and ion transporters. A linear decrease in growth was observed with decreasing omega-3 levels. Low (0.5%) inclusion of omega-3 impaired the barrier function of the proximal intestine compared to 2% inclusion. Further, low levels of omega-3 decrease the transepithelial electrical potential across the epithelium indicating disturbed ion transport. It can be concluded that low dietary levels of omega-3 impair somatic growth and intestinal function of Atlantic salmon.